Literature review. Pricing rule alternatives for the European day-ahead market - Felix Weißensteiner (Managerial Economics)
This literature review delves into the intricate realm of pricing rules in the day-ahead electricity market, spurred by a notable surge in 2022 electricity prices. Employing a comparative analysis of uniform pricing (UP), discriminatory pricing (DP), and the Vickrey–Clarke–Groves (VCG) pricing rule, the study navigates the complexities of these mechanisms. The evaluation unveils contrasting perspectives: the political push for consumer-friendly low prices versus the efficiency aspiration for a self-regulating market. DP, minimizing average prices but increasing volatility, and VCG, excelling in productive efficiency, are pitted against UP, the prevailing yet imperfect norm. The findings underscore the nuances of each rule; DP leads to reduced average prices and heightened volatility, while VCG ensures superior productive efficiency. Despite UP’s simplicity, it prompts inefficiencies and political costs. These insights illuminate the pivotal choice faced by policymakers, balancing efficiency, fairness, and market sustainability.